Maternidad en las adolescentes de la Unidad Educativa Replica Eugenio Espejo - Orozco Chávez, Mónica Judith (2020)
Maternity in adolescence is a global problem but it is exacerbated and produces a greater impact in underdeveloped countries that is almost always associated with problems at the educational level. There are extensive discussions on the impact of maternity in the education of adolescents which point specifically to their academic performance. A descriptive, documentary study was carried out using the documentary review technique of 31 adolescent mothers from the “Eugenio Espejo” Replica Educational Unit in order to determine the effects that motherhood generates on adolescent girls. A document review sheet was applied where information was collected on the sociodemographic characteristics, academic performance and desertion of adolescent mothers between 13 and 16 years of age, the results obtained express that motherhood generates low academic performance and school dropout in adolescents Furthermore, the academic performance of the adolescent mothers of the Educational Unit "Replica Eugenio Espejo" is low, in addition to this the dropout margin of this study group is high, therefore measures must be taken to guarantee the continuity of the mothers.